Management of type 2 diabetes: consensus of diabetes organizations - Elaena Quattrocchi; Tamara Goldberg; Nino Marzella (BioExcel Publishing Ltd, 2020)
Despite the advances in diabetes management, people with diabetes are not reaching their target glycemic goals. Healthcare professionals often fail to initiate, escalate, or de-intensify therapy when indicated. There are several organizations that provide guidance on the management of diabetes to assist the practitioner in achieving improved glycemic control, and this can cause confusion to the practitioner on which organizations' guidance to follow. Diabetes mellitus is associated with an elevated risk of cardiovascular disease, and there have been studies that suggest some antidiabetic medications increase cardiovascular risk and some reduce cardiovascular risk. Diabetes organizations recommend the individualization of treatment goals and choices of drug therapy that will be safe and effective. Healthcare professionals should be knowledgeable and equipped to decide on the best treatment regimen for each of their patients with type 2 diabetes (T2D) and be familiar with how to utilize the different organizations' philosophies in treating their patients.